Development of an Android-Based Food Ordering Application Using the Bubble Sort Algorithm with Database Integration and Electronic Payment Methods - Ramadhan, Reza Pajri; Widiono, Suyud (Kirana Publisher (KNPub), 2024)
In the era of rapidly advancing technology, mobile applications have become an essential need for modern society, including in the restaurant sector, which heavily relies on speed and service efficiency. This research aims to design an Android-based application using the Kotlin method to simplify the process of ordering food and beverages in restaurants. Currently, many restaurants lack an easily accessible queue system, resulting in orders being served based on processing convenience rather than queue order, which negatively impacts service evaluations. This application is designed to enable customers to place orders quickly and efficiently, monitor order statuses, and assist restaurants in optimizing service processes. With the features offered, this application is expected to enhance customer satisfaction while supporting increased business profitability through more structured and customer-oriented service.